Myocardial Epithelial Inclusions in a Bovine Fetus - Eroksuz, Y; Karabulut, B; Akdeniz Incili, C; Kara, E; Cankaya, E; Eroksuz, H (Journal of the Hellenic Veterinary Medical Society, 2025)
Myocardial Epithelial Inclusions were presented with gross, histopathological, and immunohistochemical findings in a 6-month-old aborted Simmental breed fetus. A distinct, circular, unencapsulated white lesion, measuring up to 2.5 mm in diameter was detected on the free wall of the left ventricular myocardium. Histopathological examination revealed a densely cellular focus with tubular, ductular, or acinar structures surrounded by abundant collagen. As a result, it is important to accurately identify MEIs to prevent misinterpretation of this lesion during postmortem examinations.